2009
DOI: 10.1007/s11164-008-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of trichloroethylene using N-doped TiO2 prepared by a simple sol–gel process

Abstract: Visible-light-driven N-doped TiO 2 was prepared by a simple sol-gel process using nitric acid not only as the acid catalyst of the sol-gel reaction but also as the source of nitrogen. The photocatalytic performance of the N-doped TiO 2 was investigated by using FTIR spectroscopy to monitor the degradation of trichloroethylene (TCE) during UV and visible irradiation. The photocatalytic degradation of TCE was well-reproduced several times. The activity of Ti-O-N species was supported experimentally. The N-doped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 31 publications
4
36
0
1
Order By: Relevance
“…These results indicate that the amount of nitric acid affected the particle size and crystallization of During irradiation with visible light, TCE was degraded and CO, CO 2 , HCl, and COCl 2 were generated, similarly to during UV irradiation. However, no DCAC was found in this case, similar to results reported elsewhere [5,20].…”
Section: Mechanism Of Nitrogen Dopingsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicate that the amount of nitric acid affected the particle size and crystallization of During irradiation with visible light, TCE was degraded and CO, CO 2 , HCl, and COCl 2 were generated, similarly to during UV irradiation. However, no DCAC was found in this case, similar to results reported elsewhere [5,20].…”
Section: Mechanism Of Nitrogen Dopingsupporting
confidence: 92%
“…We have prepared N-doped TiO 2 by the sol-gel method using a large amount of nitric acid as the source of nitrogen [20] as Dong et al previously reported [21]. A large amount of nitric acid was required because most of it was evaporated during the heating process.…”
Section: Introductionmentioning
confidence: 99%
“…During the visible irradiation, TCE was degraded and CO, CO 2 , HCl, and COCl 2 were generated as well as during the UV irradiation. However, no DCAC was found in this case similar to the results reported in a previous paper [34,44].…”
Section: Photocatalytic Degradation Of Tce During Uv and Visible Irrasupporting
confidence: 91%
“…On the other hand, we prepared the N-doped TiO 2 by the sol-gel method using a large amount of nitric acid as the nitrogen source [10,11] as Dong et al previously reported [12]. A large amount of nitric acid was required because most of it evaporated during the heating process.…”
Section: Introductionmentioning
confidence: 99%